Hero-poet and his furnishings: “signes of tradition” in Russian lyric of 19th - Ляпина, Лариса (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The article presents a study of the typical lyrical plot, representing the hero-poet in his study room. Comparative analysis of Russian lyric poems of different genres (elegy and others) and authors (Batyushkov, Pushkin, Fet, Polonsky and others) reveals the certain traditions in evolution of this plot – in comparison with the similar tradition in novel (investigated earlier by N. Nyagolova). In the beginning of 20th century these traditions can be observed in Bunin’s poetry and two poems of I. Annensky and N. Gumilev.